Innovative Islamic Religious Education Curriculum Model to Improve Religious Understanding in Schools - Ananda Indri Anisya; Juliani; Nur Hikmah; Sulistia Safitri; Tiara Melysa Br. Sembiring; Mhd Aslam Fikri Lubis (Journal of Contemporary Gender and Child Studies, 2025)
This study aims to develop an innovative Islamic Religious Education (PAI) curriculum model to improve religious understanding in schools. The research method used is a literature review by analyzing various literatures, scholarly articles, books, and documents related to the PAI curriculum and learning innovations. The study finds that an innovative PAI curriculum must combine a technology-based approach, contextual learning, and student-centered methods. This model also emphasizes the importance of integrating Islamic values with 21st-century skills, such as critical thinking, collaboration, and problem-solving. The research results indicate that the implementation of an innovative curriculum has the potential to enhance students' understanding of Islamic teachings and their application in daily life. Thus, this study provides a theoretical foundation for developing an PAI curriculum that is relevant to the needs of learners and the challenges of the times. This model is expected to serve as a reference for educators and policymakers to improve the quality of PAI learning in schools